Hepatobiliary mucinous cystadenoma in a two year old - Soukaina Wakrim; Mohamed EL. Jdid; Ouadie Qamouss (Journal of Pediatric Surgery Case Reports, 2022)
Introduction: Mucinous cystadenomas of hepatobiliary (MCAHb) are rare and generally benign intrahepatic cystic neoplasms, only few pediatric cases were found in the literature. These lesions are clinical presentation differ significantly so they can mimic other liver lesions. Brief case report: In this case report, we discuss a 2-year-old girl who presented with abdominal pain and distended abdomen, for which she had an abdominal ultrasound (US) and Computerized tomography (CT) were objectived cystic lesion lobe multi-loculated with regular borders in the left hepatic, the diagnostic was a hydatid cyst.The histopathological exam, after a laparotomy, revealed a biliary mucinous cystadenoma. Herein, we review the current literature on biliary mucinous cystic neoplasms in pediatric population. Conclusion: The diagnosis of MCAHb is made on several parameters radiological, biochemical, serological and histological.